A Survey of the Practice of After-Hours and Emergency Endoscopy in Canada - Karuppan Chetty Muthiah; Robert Enns; David Armstrong; Angela Noble; James Gray; Paul Sinclair; Palma Colacino; Harminder Singh (Canadian Journal of Gastroenterology)
OBJECTIVE: To determine staffing and practice patterns for after-hours endoscopy service in Canada